2021
DOI: 10.1136/bmjopen-2021-051519
|View full text |Cite
|
Sign up to set email alerts
|

Impact of electronic cigarette ever use on lung function in adults aged 45–85: a cross-sectional analysis from the Canadian Longitudinal Study on Aging

Abstract: ObjectiveTo describe the sociodemographic characteristics associated with e-cigarette ever use and to examine the impact of e-cigarette ever use on lung function impairment in an ageing population.DesignA cross-sectional analysis of data from the Canadian Longitudinal Study on Aging.SettingA national stratified sample of 44 817 adults living in Canadian provinces.ParticipantsRespondents included participants aged 45–85 and residing in the community in Canadian provinces.Outcome measuresThe Global Lung Function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
0
4
1
Order By: Relevance
“…It is interesting that past or present e-cigarette users were signi cantly less likely than never e-cigarette users to demonstrate an obstructive pattern on spirometry. This is contrary to ndings in the general population reported by other groups who described increased obstruction associated with e-cigarette use even when adjusted for concurrent tobacco cigarette use (20,21). It is possible that the older age of the non-e-cigarette users (22) and their slightly higher daily cigarette intake (and probable higher total lifetime exposure to cigarettes) could have contributed to their higher rate of obstruction.…”
Section: Discussioncontrasting
confidence: 84%
“…It is interesting that past or present e-cigarette users were signi cantly less likely than never e-cigarette users to demonstrate an obstructive pattern on spirometry. This is contrary to ndings in the general population reported by other groups who described increased obstruction associated with e-cigarette use even when adjusted for concurrent tobacco cigarette use (20,21). It is possible that the older age of the non-e-cigarette users (22) and their slightly higher daily cigarette intake (and probable higher total lifetime exposure to cigarettes) could have contributed to their higher rate of obstruction.…”
Section: Discussioncontrasting
confidence: 84%
“…Alternative forms of nicotine intake have similar harmful effects of altering airflow through the airways as smoking cigarettes and, therefore, may not be a healthier alternative to smoking [30]. Other authors recognized that using an e-cigarette for 5 min causes an increase in peripheral airway resistance, increased impedance, and oxidative stress and considered it an important clinical effect [31].…”
Section: Cigarette Smokers N=20mentioning
confidence: 99%
“…The available literature has found few epidemiological studies examining the long-term effects of e-cigarette use, both in young people who start smoking e-cigarettes and in smokers who switch to exclusive use of e-cigarettes. [31].…”
Section: Cigarette Smokers N=20mentioning
confidence: 99%
“…The following factors other than tobacco use affecting the occurrence of outcomes that were used in past crosssectional studies investigating the relationship of e-cigarette or HTP use to the occurrence of outcomes (COPD, 12,[16][17][18][19][20][21][22] asthma, 12,16,18,20,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] wheezing, 13,32,[39][40][41][42][43] breath shortness/cough/phlegm, 32,33,41,42 lung function abnormality 44 ) and cohort study 45 investigating the relationship between smoking and COPD were used as adjustment factors in this study: age, sex, BMI, resident area population size, education level, household income, whether employed or unemployed, lifestyle habits (frequency of exercise, frequency of alcohol drinking, level of stress), whether historical or concurrent diseases were present (diabetes, lipid abnormality, hypertension, stroke, allergic dermatitis/rhinitis, angina pectoris, coronary heart diseases (CHD)). Information about passive smoking was not obtained in this study, because no statistical effect from passive smoking was observed 16,39 in past cross-sectiona...…”
Section: Confounding Factorsmentioning
confidence: 99%